1974
DOI: 10.1111/j.1365-3180.1974.tb01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of paraquat on crop establishment in killed swards

Abstract: Summary: Résumé: Zusammenfassung The establishment of crops direct‐drilled after various times into swards treated with paraquat (1,1′‐dimethyl‐4,4′‐bipyridylium‐ 2/A) was examined. Best results with Brassica napus and B. oleracea were obtained with 1–1 kg/ha applied 7 days before drilling and 2–3 kg/ha applied 14 days before. Although delaying drilling from 7 to 14 days after application reduced the phytotoxicity, the higher dose was needed when drilling was delayed, to reduce competition from the sward regro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1975
1975
1981
1981

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In these experiments both germination and growth were affected and grasses were more susceptible than dicotyledons. Covering seeds with a mulch of grass clippings that had been previously sprayed with paraquat has also been shown to reduce germination and seedling growth (Warboys 1974;Klingman and Murray, 1976). Thus it is well established, as confirmed by the experiment reported in this paper, that 'second-hand' paraquat can be toxic to grass seedlings.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In these experiments both germination and growth were affected and grasses were more susceptible than dicotyledons. Covering seeds with a mulch of grass clippings that had been previously sprayed with paraquat has also been shown to reduce germination and seedling growth (Warboys 1974;Klingman and Murray, 1976). Thus it is well established, as confirmed by the experiment reported in this paper, that 'second-hand' paraquat can be toxic to grass seedlings.…”
Section: Discussionsupporting
confidence: 67%
“…When paraquat has been sprayed on to an old grass sward or stubble, residues of the herbicide are present in the dying herbage, in organic dehris or on the soil surface. These residues are potentially toxic to germinating seedlings (Warboys, 1974;Klingman and Murray, 1976). There is therefore a risk of herbicide damage to grasses that are direct-drilled after spraying with paraquat.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have reported that paraquat residues in surface plant litter can adversely affect seedling development in mineral soils (1,2,9,11,21,22). However, the impact of clipping debris containing herbicide residues on seedling development has only been briefly studied under greenhouse conditions (11).…”
Section: Resultsmentioning
confidence: 99%
“…. Several investigators have reported paraquat toxicity on mineral soil sites where herbicide residues were present in surface litter (1,2,9,11,21,22,24)._ Emerging seedlings absorbed paraquat fn;>m plant h~ter lay• ers at the soil surface, but covenng seed with soil or incorporation of soil into the surface litter ~e duced the extent of herbicide injury. Surface disturbance of organic soils or introduction of clay into them also reduced paraquat residual activity due to the transfer of weakly adsorbed paraquat in peat wils to incorporated clays which inactivated paraquat (8,23).…”
mentioning
confidence: 99%